A comparative analysis between General Data Protection Regulations and California Consumer Privacy Act - Syed Khurram Hussain Naqvi; Komal Batool (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2023)
Data breach is a common phenomenon is these days. Entities holding the personal data are involved in providing data to marketing and other companies for their benefit. Consequently, the citizens suffer and pay the price of breaching. Various countries have adopted personal data protection laws in line with General Data Protection Regulations (GDPR). The California State has also made legislation to secure consumer rights in respect of personal data. This study made a comparison between General Data Protection Regulation (GDPR) and California Consumer Privacy Act (CCPA). After study, it has been identified that GDPR is a comprehensive document which can be used for providing security of personal data around the world. It has all the relevant clauses/ Articles that can be used accordingly. Furthermore, being dynamic in nature it has the capability to become adoptable to new changes/ technologies. However, there is a need to expend the scope of the study and conduct a comparative analysis on the basis of geographical boundaries. The future directions may include the study of laws relating to personal data protection of various developing countries in the context of the GDPR.